2022
DOI: 10.1111/ajt.17121
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough COVID-19 cases despite prophylaxis with 150 mg of tixagevimab and 150 mg of cilgavimab in kidney transplant recipients

Abstract: The cilgavimab−tixagevimab combination retains a partial in vitro neutralizing activity against the current SARS‐CoV‐2 variants of concern (omicron BA.1, BA.1.1, and BA.2). Here, we examined whether preexposure prophylaxis with cilgavimab−tixagevimab can effectively protect kidney transplant recipients (KTRs) against the omicron variant. Of the 416 KTRs who received intramuscular prophylactic injections of 150 mg tixagevimab and 150 mg cilgavimab, 39 (9.4%) developed COVID‐19. With the exception of one case, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 15 publications
1
76
0
Order By: Relevance
“…It included studies from the United States, France, Israel, Belgium, Spain and the United Kingdom. This review included ten retrospective cohort studies 12,[16][17][18][19][20][22][23][24][25] (including two preprints 16,20 ), six prospective, observational cohort studies [26][27][28][29][30][31] (also including one preprint…”
Section: Resultsmentioning
confidence: 99%
“…It included studies from the United States, France, Israel, Belgium, Spain and the United Kingdom. This review included ten retrospective cohort studies 12,[16][17][18][19][20][22][23][24][25] (including two preprints 16,20 ), six prospective, observational cohort studies [26][27][28][29][30][31] (also including one preprint…”
Section: Resultsmentioning
confidence: 99%
“…The authorization of T/C coincided with the emergence of the Omicron variant, which resulted in previously effective monoclonal antibodies losing effectiveness. 4 5 6 7 There is limited data available on the real-world effectiveness of T/C, especially in the Omicron era. T/C requires significant resources for administration due to its EUA status and associated institutional requirements for administering it.…”
Section: Introductionmentioning
confidence: 99%
“…The PROVENT study demonstrated a persistent neutralizing activity against pre-omicron variants for 6 months after tixagevimab-cilgavimab administration despite a progressive decrease in drug concentration. 4 As the neutralizing activity is already reduced against the omicron variant in vitro and in vivo one month after the injection [5][6][7] , the significant decrease in anti-RBD titers indicate a potential rapid loss of efficacy and an increased risk of severe COVID-19 in transplant recipients. Despite the fact that all of the sera tested within 4−5 months after a 150 mg dose of tixagevimab and cilgavimab each exhibited neutralizing activity against BA.2,it should be kept in mind that the currently predominant variant (BA.5) is characterized by a higher resistance against tixagevimab-cilgavimab.…”
mentioning
confidence: 99%